Core inflation in the euro area: An application of the generalized dynamic factor model - Elke Hahn (Goethe University Frankfurt, Center for Financial Studies (CFS), 2002)
Since the second half of the nineties the euro area has been subject to a considerable accumulation of temporary and idiosyncratic price shocks. Core inflation indicators for the euro area are thus of utmost interest. Based on euro area-wide data core inflation in this paper is analyzed by means of an indicator derived from the generalized dynamic factor model. This indicator reveals that HICP inflation strongly exaggerated both the decline as well as the increase in the price trend in 1999 and 2000/2001. Our results reinforce those achieved by Cristadoro, Forni, Reichlin and Versonese (2001) based on euro area country data which indicates the robustness of the indicator.
urn:nbn:de:hebis:30-10018
Keywords: C33; E31; 330; Core Inflation; Euro Area; Generalized Dynamic Factor Model; Principal Component Analysis